Atheroprotective Effects and Molecular Mechanism of Berberine - Xing, Lu; Zhou, Xin; Li, Ai-Hong; Li, Hui-Jin; He, Chun-Xia; Qin, Wei; Zhao, Dong; Li, Peng-Quan; Zhu, Li; Cao, Hui-Ling (Frontiers in Molecular Biosciences, 2021)
Cardiovascular diseases remain the leading cause of morbidity and mortality worldwide. Atherosclerosis is the main pathological basis of cardiovascular diseases and it is closely associated with hyperlipidemia, endothelial injury, macrophage-derived foam cells formation, proliferation and migration of vascular smooth muscle cells (VSMCs), platelet aggregation, and altered gut microbiota. Various symptomatic treatments, that are currently used to inhibit atherosclerosis, need to be administered in long term and their adverse effects cannot be ignored. Berberine (BBR) has beneficial effects on atherosclerosis through regulating multiple aspects of its progression. This review highlights the recent advances in understanding the anti-atherosclerosis mechanism of BBR. BBR alleviated atherosclerosis by attenuation of dyslipidemia, correction of endothelial dysfunction, inhibition of macrophage inflammation and foam cell formation, activation of macrophage autophagy, regulation of the proliferation and migration of VSMCs, attenuation of platelet aggregation, and modulation of gut microbiota. This review would provide a modern scientific perspective to further understanding the molecular mechanism of BBR attenuating atherosclerosis and supply new ideas for atherosclerosis management.